PEMBELAJARAN MATEMATIKA BERBASIS KECERDASAN MAJEMUK - Aep Sunendar (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2017)
This article is the result of a study of how to design mathematical learning based onthe combination of each student's intelligence. One important step to achieve successin the learning process is to prepare in advance how a lesson will be implemented.Preparation is done by the teacher by making the planning, preparing step / scenariolearning and prepare the tools, media and assessment needed to support the learningprocess to be implemented. In addition, teachers must also consider the potential ofstudents. One of the potentials of students is the potential of multiple students.Multiple intelligence can be empowered in planning learning to achieve the expectedlearning competencies, including in mathematics learning.